Gas-Screen Slotted Quartz Tube Atomic Absorption Spectrometry: A Remedy for Reducing Interference Effects of Calcium and Chromium - Gholami, M.; Yosefi, M. H.; Behkami, S.; Olyai, M. R. Talei Bavil; Arslan, Y.; Bakirdere, S.; Ataman, O. Y. (TAYLOR & FRANCIS INC, 2013)
A simple device for the reduction of nonspectral interferences in flame atomic absorption spectrometry is proposed. It has been reported that the use of a gas screen (GS) system together with a slotted quartz tube (SQT) enhances the residence time of analyte atoms in measurement zone even more than the SQT alone. This combination causes enhancement of sensitivity and improves the reproducibility of absorbance measurements. In addition, it protects the optical windows of the atomic absorption spectrometer. The operational mechanism of gas screen is simply applying two argon gas walls at both ends of SQT to provide an environment that is partly protected from air. This action enhances the sensitivity of measurement. In this study, interference effects of excess amounts of calcium and chromium on the measurements of Cd, Co, Cu, Pb, Mn, Ni, Se, and Zn were studied using flame AAS. The presence of both Ca and Cr cause higher absorbance values; it is suggested that this is due to formation of oxide species of Ca and Cr and as a result analyte oxide production is suppressed. Therefore, analyte free atom population and sensitivity are enhanced. This enhancement results in a positive error in measurements. For instance, presence of solely 8.0mgL1 of Cr or Ca for Pb as the analyte enhances the signals by 75% and 56%, respectively. When SQT or GS-SQT is used, this effect is significantly reduced.
Keywords: Flame atomic absorption spectrometry; Gas screen slotted quartz tube; Nonspectral interference; CADMIUM; LEAD; PRECONCENTRATION; TRAPS; Chemistry